Transformational Leadership Style in Increasing Economic Sustainability in the Banking Sector - Novianti, Novianti; Wulandari, Dini; Suyoko, Dwi Setyo; Perdana, Mirwan Surya (LifeSciFi, 2024)
One of the crucial challenges facing the banking sector currently is Human Resources (HR) management, especially the management of millennial generation employees, who are an essential part of the current workforce. The millennial generation is also expected to drive economic sustainability in the banking sector. This research is aimed to explore the influence of transformational leadership style on the performance of millennial generation employees with self-efficacy as mediation. The object and population of this research are millennial generation employees at PT. Bank Rakyat Indonesia, Persero (Tbk) Semarang Regional Office. Purposive sampling was used to choose participants from the millennial demographic, resulting in a total sample size of 106 employees (N=106). A closed questionnaire given to research participants provided the data. This research employs a quantitative methodology. Using Smart PLS 3 software, data were analyzed using the Partial Least Square (PLS) technique. The result revealed a clear correlation between transformational leadership styles on the performance of millennial employees. Through self-efficacy as a mediator, the transformational leadership style has an indirect impact on worker performance. The research results can be used as important information for managerial-level leaders of organizations in the banking sector to implement a leadership style appropriate for millennial generation employees to achieve high performance.